Exploring Hazard Risks and People’s Adjustment: A Study in the Downstream of the Padma Multipurpose Bridge Project - Khan, Md Fahim Azraf (Brac University, 2022)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2022.